Gradual South‐North Climate Transition in the Atlantic Realm Within the Younger Dryas. Issue 8 (21st April 2021) - Zhang, Haiwei; Cheng, Hai; Spötl, Christoph; Zhang, Xu; Cruz, Francisco W.; Sinha, Ashish; Auler, Augusto S.; Stríkis, Nicolás M.; Wang, Xianfeng; Kathayat, Gayatri; Li, Xianglei; Li, Hanying; et al.
Abstract: The abrupt climate event Younger Dryas (YD) has been extensively studied; however, its structure is still poorly understood. Climate in northeastern Brazil is very sensitive to the latitudinal position of the intertropical convergence zone (ITCZ) associated with abrupt climate change in the Atlantic. Here, we report changes in the ITCZ position within the YD by using precise speleothem multiproxy records from northeastern Brazil. We provide evidence for a gradual northward migration of the ITCZ preceding poleward shifts of the westerlies and the polar front in northern high latitudes within the YD. This can be attributed to gradual increase in atmospheric CO2 concentration as a consequence of the weakening Atlantic Meridional Overturning Circulation (AMOC). We suggest that a persistent increase in atmospheric CO2 might have triggered a resumption of the AMOC and reorganization of the atmosphere circulation in the Atlantic during the mid‐YD. Plain Language Summary: The Younger Dryas (YD) is the most recent millennial‐scale abrupt climate event in Earth history. Although its origin has been extensively studied, its structure is still poorly understood. Climate in northeastern Brazil is very sensitive to the latitudinal position of the intertropical convergence zone (ITCZ) responds to abrupt climate change in the Atlantic (e.g., YD). By using stable isotope and trace element proxy records of speleothem from Toca da Boa Vista Cave, northeastern Brazil, together with other paleoclimatic records in the Atlantic realm, we provide evidence for a gradual northward migration of the ITCZ preceding poleward shifts of the westerlies and the polar front in northern high latitudes within the YD. This can be attributed to a gradual increase in atmospheric CO2 concentration under the situation of weakening Atlantic Meridional Overturning Circulation (AMOC). A persistent increase in atmospheric CO2 concentration might have triggered a resumption of the AMOC and reorganization of the atmosphere circulation in the Atlantic during the mid‐YD. Key Points: Speleothem and other paleoclimate records confirm a wet climate in tropical South America within the Younger Dryas Precise speleothem multiproxy records reflect a bipartition of the Younger Dryas precipitation in northeastern Brazil Gradual South‐North climate transition in the Atlantic responded to a gradual increase in atmospheric CO2 within the YD